2004
DOI: 10.4269/ajtmh.2004.71.471
|View full text |Cite
|
Sign up to set email alerts
|

Duplex Doppler Sonographic Assessment of the Effects of Diethylcarbamazine and Albendazole Therapy on Adult Filarial Worms and Adjacent Host Tissues in Bancroftian Filariasis

Abstract: We used duplex Doppler sonography to assess effects of diethylcarbamazine and albendazole therapy (DEC/ALB) on adult Wuchereria bancrofti in vivo. The study was performed in clinically normal Egyptian adults with blood microfilaria counts > 80/mL. Motile adult worms were observed before treatment in dilated scrotal lymphatic vessels in 28 of 36 men (78%) and over the proximal extremities in 5 of 22 women (23%). Most worm nests were inactivated in the months following treatment (90% at 12 months). Circulating f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
25
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…13,39 In our study, for MF−/Og4C3− children who received drugs containing DEC, significant decreases ( P < 0.001) in antibody responses to Bm14 and Bm33 occurred as early as time point B ( Figures 1A and 2A ) whereas Og4C3+ children who received drugs containing DEC did not show significant decreases ( P < 0.001) in antibody responses to Bm14 until time point C ( Figure 1B ). MF+/Og4C3+ children, those with the highest antigen levels before treatment, showed no significant decrease in antibody responses to either Bm14 or Bm33 at any time point regardless of whether active drug was received ( Figure 3A and B ).…”
Section: Discussionmentioning
confidence: 78%
“…13,39 In our study, for MF−/Og4C3− children who received drugs containing DEC, significant decreases ( P < 0.001) in antibody responses to Bm14 and Bm33 occurred as early as time point B ( Figures 1A and 2A ) whereas Og4C3+ children who received drugs containing DEC did not show significant decreases ( P < 0.001) in antibody responses to Bm14 until time point C ( Figure 1B ). MF+/Og4C3+ children, those with the highest antigen levels before treatment, showed no significant decrease in antibody responses to either Bm14 or Bm33 at any time point regardless of whether active drug was received ( Figure 3A and B ).…”
Section: Discussionmentioning
confidence: 78%
“…However, no impact of 12-day DEC treatment was seen on the size of hydroceles in treated patients in a placebo-controlled study in Tanzania (Bernhard et al 2001). Hussein et al (2004) observed no change in prevalence rates of non-palpable hydroceles and intra-scrotal calcifications, detectable by ultrasound, 2 years after treatment with DEC plus albendazole.…”
Section: Discussionmentioning
confidence: 95%
“…Although MF loads (and presumably the Wolbachia load) are reduced post-treatment compared with pre-treatment levels, the levels of circulat- ing antigens (when able to be measured) remained no different ( Table 1 ). The DEC treatment studies (with or without albendazole) have shown antigenemia to be 23-57% of pretreatment levels with wide variations [39][40][41][42][43] likely because of the only moderate macrofilaricidal activity of DEC. [44][45][46][47] Similarly, doxycycline treatment resulted in lower levels of antigenemia at 12 months and 24 months post-treatment compared with pretreatment levels. 7,48 Nevertheless, a longitudinal study monitoring levels of circulating filarial antigens in parallel with the pro-angiogenic factors in both the microfilaraemic individuals and those with lymphedema and/or elephantiasis could provide a more definitive answer to this issue.…”
Section: Discussionmentioning
confidence: 99%